Sleep disturbance among Malaysian patients with end-stage renal disease with pruritus - Rehman, Inayat Ur; Lai, Pauline Siew Mei; Lim, Soo Kun; Lee, Learn Han; Khan, Tahir Mehmood (BioMed Central, 2019)
Background: Chronic kidney disease-associated pruritus (CKD-aP) is a well-recognized, frequent and compromising complication among patients on hemodialysis. Despite advancement in basic medical sciences, CKD-aP is still a major complication and a challenge for both physicians and patients to manage. The aim of this study was to estimate the prevalence of CKD-aP among hemodialysis patients in Malaysia, to determine the impact of CKD-aP on sleep quality and any factors associated with CKD-aP. Method: A multi-centered, cross-sectional study design was conducted from February 2017 to September 2017 at a tertiary hospital and its affiliated dialysis centers, in Kuala Lumpur, Malaysia. Included were patients > 18 years of age who were undergoing hemodialysis and could understand Malay. Participants were asked to fill the Malay 5D-itch scale and the Malay Pittsburgh sleep quality index (PSQI) upon recruitment. Results: A total of 334/334 patients were recruited (response rate = 100%). The majority were male (59.6%) and Chinese (61.7%). A total of 61.3% had pruritus, of which most patients (63.4%) reported that their pruritus was mild. More than half (54.1%) reported that they slept > 6 h, and 93.2% experienced no sleep disturbances during the night. However; the overall PSQI median score [IQR] was 6.0 [5.0-9.0]. No significant association was found between demographic and clinical characteristics of patients with the severity of pruritus. Patients with moderate to severe pruritus were found to be 5.47 times more likely to experience poor sleep quality as compared to patients with mild or no pruritus. Conclusion: In Malaysia, the prevalence of CKD-aP was 61.3%, of which the majority reported that their pruritus was mild. Patients with moderate to severe pruritus were found to be 5.47 times more likely to experience poor sleep quality as compared to patients with mild or no pruritus. © 2019 The Author(s).